Dog's colorful day : a messy story about colors and counting - Dodd, Emma, 1969- ([New York?] : Puffin Books, 2003)
In this colorful story of a sloppy dog, you can count on a happy ending.
Originally published in the United States: New York : Dutton Children's Books, c2001.
Keywords: Dogs -- Fiction; Color; Counting